Analisa Kecepatan Angin Di Jalan Jendral Sudirman Kota Pekanbaru - Imalatunil Khaira; Aryo Sasmita; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Transportation is the most influential source in increasing levels of carbon monoxide (CO) in the air. Pekanbaru is the capital of Riau province which is experiencing rapid economic development that is a cause of population growth and increasing the number of motorized vehicles. The purpose of this study is to measure CO concentrations from mobile sources then compare them with PP No. 41 of 1999, calculating CO concentrations with the Gaussian Line Source Model, and mapping the predicted distribution of CO emissions on Jalan Jendral Sudirman, Pekanbaru City. The method used is counting the number of motorized vehicles, measuring the concentration of CO in the field, and measuring wind speed in the field. Based on the results of research that has been done, it can be concluded that the highest wind speed is in front of Sudirman Square on Thursday at 3.0 m / s while the lowest wind speed is in front of the Ramayana at 0.5 m / s on Tuesday and Wednesday.Keywords: Wind Speed, Jalan Jendral Sudirman